2017
DOI: 10.1038/onc.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and posttranscriptional regulation of HOXA13 by lncRNA HOTTIP facilitates tumorigenesis and metastasis in esophageal squamous carcinoma cells

Abstract: The long non-coding RNA, HOTTIP, has an important role in tumorigenesis. It is known that HOTTIP regulates HOX gene family; however, its regulatory mechanism in esophageal squamous cell carcinoma (ESCC) remains elusive. In this study, we investigated the role of HOTTIP in ESCC and observed that HOTTIP/HOXA13 was upregulated in ESCC and promoted cell proliferation and metastasis in vivo and in vitro. Interestingly, harboring a miR-30b-binding site, HOTTIP as a molecular sponge mainly regulated miR-30b level in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 42 publications
2
108
1
1
Order By: Relevance
“…Accumulating studies reveal that HOTTIP has been up‐regulated in a multitude of diseases . However, we failed to detect an aberrant expression of HOTTIP in fibrotic livers.…”
Section: Discussioncontrasting
confidence: 73%
“…Accumulating studies reveal that HOTTIP has been up‐regulated in a multitude of diseases . However, we failed to detect an aberrant expression of HOTTIP in fibrotic livers.…”
Section: Discussioncontrasting
confidence: 73%
“…20,21,24,28 Recently, Liao et al 22 demonstrated that HOTTIP expression is elevated in coronary artery disease and in tumor necrosis factor-α or platelet-derived growth factor-induced proliferating endothelial cells; moreover, ectopic expression of HOTTIP augments endothelial cell proliferation. Studies have revealed that HOTTIP is highly expressed in small-cell lung cancer, colorectal cancer, pancreatic cancer, and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…29 PKM2, which catalyzes the last step of glycolysis, has a critical role in tumor cell proliferation. 23,24 To investigate the mechanism of HOTTIP in ischemic stroke, we determined the relationship between HOTTIP and miR-143. These results suggest that HOTTIP overexpression not only attenuates OGD-induced cell injury but also ameliorates the impaired glycolytic process in primary neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HOTAIR promotes cell invasion and metastasis, and epithelial to mesenchymal transition by acting as a miR‐148a sponge to regulate Snail2 expression in esophageal cancer 20. Moreover, over‐expressed HOTTIP promotes cell proliferation and metastasis through acting as a miR‐30b sponge and interacting with WDR5 to modulate the expression of HOXA13 and Snail 1in ESCC cells 21. In addition, LUCAT1 was found to be significantly upregulated in ESCC, and promote the formation and metastasis of ESCC through regulating the stability of DNMT1 and repressing the expression of tumor suppressors 22.…”
Section: Introductionmentioning
confidence: 99%